KAJIAN TERHADAP FUNGSI ANGGARAN DALAM PEMBANGUNAN EKONOMI PEMERINTAHAN DAERAH - Abdul Rahman Suleman; Abdurrozzaq Hasibuan (Universitas Islam Islam Sumatera Utara, 2018)
This paper is to analyze the budgeting system and its function to develop financial development. This qualitative study employs the document analysis as an instrument to collect data, and hence, this study is categorized as library research. The buddgetting system is strategic element for developing economic sectors, and is utilized as a means for advocacy and controlling towards whether financial income or outcome of the district, region or nation, especially for upcoming periode. Therefore, it is also as sources for continuous development expenses which is clearly targeting achievement and measureable. However, budgeting sytem faces barriers and weaknesses such as political context, legal context, economic conditions, and historical context. Allocating budget as such away further give impact multiplier to enhance the regional income and contribute to spread effect among the society.